The Information security tools in an automated system for secure information exchange : Information security tools in an automated system for secure information exchange (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
The article presents information security tools to ensure the secure exchange of information in an automated system. A model of information security for an automated information exchange system is proposed. This model will increase the level of information security in electronic document flow in the cross-border space.